Effects of Probiotic Bacteria Lactobacillaceae on the Gut Microbiota in Children With Celiac Disease Autoimmunity: A Placebo-Controlled and Randomized Clinical Trial - Oscarsson, Elin; Håkansson, Åsa; Andrén Aronsson, Carin; Molin, Göran; Agardh, Daniel (Frontiers in Nutrition, 2021)
Disturbances of the gut microbiota may influence the development of various autoimmune diseases. This study investigated the effects of supplementations with the probiotic bacteria, Lactiplantibacillus plantarum HEAL9 and Lacticaseibacillus paracasei 8700:2, on the microbial community in children with celiac disease autoimmunity (CDA). The study included 78 genetically predisposed children for celiac disease with elevated levels of tissue transglutaminase autoantibodies (tTGA) signaling for ongoing CDA. Among those children, 38 received a placebo and 40 received the probiotic supplement daily for 6 months. Fecal and plasma samples were collected at baseline and after 3 and 6 months, respectively. The bacterial community was investigated with 16S rRNA gene sequencing and terminal restriction fragment length polymorphism (T-RFLP), and tTGA levels were measured in radiobinding assays. In children that received probiotic supplementation, the relative abundance of Lactobacillaceae increased over time, while it remained unchanged in the placebo group. There was no overall correlation between tTGA levels and bacterial genus except for a positive correlation between Dialister and IgG-tTG in the probiotic group. The abundance of specific bacterial amplicon sequence variant (ASV:s) changed during the study in both groups, indicating that specific bacterial strains might be affected by probiotic supplementation.